(untitled) (Agriculture, Food, and Natural Resources Journal, 2025)
This study evaluated the effect of storage period on the phytochemical and anti-nutrient contents of fresh and canned milky Calocybe indica stored for six weeks. Freshly cultivated mushrooms were washed, cut into 5 cm sizes, and canned in brine solutions containing varying ratios of salt and citric acid (2.0:1.5, 2.5:1.5, 3.0:1.5, and 3.5:1.5). Each can weigh approximately 190g. Phytochemical and anti-nutrient compositions were analysed weekly using standard methods. Data were subjected to one-way analysis of variance (p < 0.05). The phytochemical results (%) ranged as follows: total phenol (7.07–24.54), flavonoids (20.20–29.17), glycosides (0.02–0.34), alkaloids (0.11–2.67), total antioxidants (3.01–4.39), and ferric reducing antioxidant power (0.22–0.68). Anti-nutrient values (%) for tannins, phytates, saponins, and oxalates ranged from 0.04–0.29, 0.11–0.89, 0.06–0.54, and 0.23–0.44, respectively. Canning significantly reduced all parameters except flavonoids, which increased. During storage, most phytochemicals and anti-nutrients decreased significantly, though total phenol, total antioxidants, and ferric reducing antioxidant power increased with higher sodium chloride concentrations in the brine. The brine solution had little effect on other parameters. The study concludes that storage time influenced the anti-nutrient composition, with levels remaining below harmful thresholds, confirming the mushrooms’ safety for consumption. Overall, canning and subsequent leaching of phytochemicals into the brine contributed to notable phytochemical losses over time.